Caspase‐14 overexpression in hairless mice is not involved in utricle formation. Issue 7 (25th June 2013) - Devos, Michael; De Groote, Philippe; Gilbert, Barbara; Bruggeman, Inge; Leurs, Kirsten; Lippens, Saskia; Vandenabeele, Peter; Declercq, Wim
Abstract Loss of functional hairless (HR) transcriptional repressor leads to utricle formation and congenital hair loss both in mice and men. Studies in mice have shown that this is preceded by overexpression of caspase‐14 at the infundibulum in the hair follicle before conversion to utricle occurs. In this report, we show that HR regulates caspase‐14 expression dependent on its interaction with histone deacetylases, implicating chromatin remodelling in the transcriptional regulation of caspase‐14. However, crossing hairless mutant mice with caspase‐14‐deficient mice revealed that caspase‐14 overexpression is not the cause of utricle formation.